Intermodel Spread in the Northern Hemisphere Stratospheric Polar Vortex Response to Climate Change in the CMIP5 Models. Issue 22 (16th November 2019) - Wu, Yutian; Simpson, Isla R.; Seager, Richard
Abstract: This study investigates the intermodel spread of the Northern Hemisphere winter stratospheric polar vortex change to anthropogenic greenhouse gas increase in Coupled Model Intercomparison Project Phase 5 (CMIP5) models. Previous proposed mechanisms for the polar vortex response to climate change, based on analysis of atmosphere‐only models, are found inadequate to explain the intermodel spread in the coupled models in CMIP5. It is further found that resolved stationary wave driving in the polar vortex region accounts for less than 30% of the intermodel spread, and intermodel differences in both the vertical and meridional wave propagation contribute to differences in the wave driving. The results call for a detailed budget analysis of the stratospheric circulation response by including both the resolved and parameterized processes through the Dynamics and Variability Model Intercomparison Project. The results also highlight a need for an improved theoretical understanding of future projected polar vortex change and intermodel spread. Plain Language Summary: It has been increasingly recognized that the stratospheric circulation can significantly affect the troposphere and the surface through a downward influence, and thus, it is important to predict and understand how the stratospheric circulation will respond to anthropogenic greenhouse gas increase. However, there is a large disagreement in the stratospheric circulation response to climate change among the current generation of climate models. This study determines that previously proposed mechanisms to explain the intermodel spread are inadequate and, therefore, motivates an improved understanding of the stratospheric circulation response and model‐to‐model differences. This is a goal that should be achieved through forthcoming model intercomparison efforts. Key Points: Resolved stationary wave driving accounts for less than 30% of the intermodel spread in the stratospheric polar vortex change in CMIP5 Both altered vertical wave propagation into the stratosphere and altered meridional propagation within the stratosphere contribute Proposed theories for the stratospheric polar vortex response to climate change appear inadequate to explain the intermodel spread in CMIP5